Recent Advances in the Synthesis and Reactivity of Vinylallenes - Afonso, María M.; Palenzuela, J. A. (Current Organic Chemistry, 2019)
Vinylallenes have been synthesized and used as reagents for many years. However, the number of reviews covering the advances in the chemistry of vinylallenes are scarce. Most of the information lies in general reviews about allenes or in reviews dedicated to specific areas of research. Today, vinylallenes are used in the synthesis due to the special characteristics of this moiety, a diene with a non-conjugated double bond and the capacity to generate axial chirality. In this review, the most relevant publications involving vinylallenes, published in the last fifteen years, are compiled. The review includes new or improved synthetic methods and the reactivity of vinylallenes prepared by classical or new methods. The reactions of vinylallenes have been classified as Nazarovtype processes, cycloaddition reactions, and reactions in which vinylallenes are key intermediates, usually non-isolated but essential for the process to occur. Other types of reactivity are also included.
Keywords: penta-1; 2; 4-trienes